Human work interaction design for pervasive and smart workplaces - Campos, Pedro F. (2022)
Pervasive and smart technologies have pushed work place configuration beyond linear logic and physical boundaries. As a result, workers’ experience of and ac cess to technology is increasingly pervasive, and their agency constantly reconfigured. While this in certain areas of work is not new (e.g., technology mediation and decision support in air traffic control), more recent developments in other domains such as healthcare (e.g., Augmented Reality in Computer Aided Surgery) have raised challenging issues for HCI researchers and practitioners. The question now is: how to improve the quality of workers’ experience and outputs? This workshop focuses on answering this question to support professionals, academia, national labs, and industry engaged in human work analysis and interac tion design for the workplace. Conversely, tools, proce dures, and professional competences for designing hu man-centered technologies for pervasive and smart workplaces will be discussed.